An Exploration of Iran's Banking System Based on Islamic-Social Banking Principles with an Emphasis on Improving Social Capital (Bank Sepah Case Study) - Mohammad Reza Yazdanpanah; Keramatollah Rasekh; Majid Reza Karimi (تحقیقات مالی اسلامی (پیوسته))
Islamic banking is a model of banking that is implemented along with Islamic law and aims to achieve social development through moral investment. Banks as money market institutions can play an undeniable role in economic and social categories such as urban development, participation in environmental protection, establishment of medical centers, etc. The present study was designed and conducted with the aim of exploring the Iranian banking system based on the principles of Islamic-social banking with emphasis on improving social capital, case study: Sepah Bank. The method of the present study was mixed and implemented qualitatively and quantitatively. The statistical population of the present study in the qualitative part included experts aware of the subject of research and in the quantitative part included all the heads and deputies of Sepah Bank and former Ansar Bank branches in Shiraz. The research data collection tools included a researcher-made interview and a questionnaire. In order to analyze the data of the present study, coding in the qualitative part and structural equation test and t-test in the quantitative part were used. The whole process of data analysis was performed in SPSS and PLS software. In general, it was determined that in the formation of Islamic-social banking, while trying to create desirable behaviors, cultural issues, internal excellence, motivational system and managerial transformation; Provided conditions for solving the problems of micro and macro factors. Also, according to the results of the present study, it can be determined that attention to short-term, medium-term and long-term strategies is necessary and important that should be seriously pursued. Undoubtedly, paying attention to the principles of Islamic-social banking and trying to implement it can lead to consequences in the social, Islamic and banking fields.